Amino acid-based biostimulant improves the productivity of Radish (Raphanus sativus L.) under saline stress - Jesus, Angela Lucena Nascimento de (2023)
The radish culture is highly sensitive to salinity. The use of an amino acid-based biostimulant can, therefore, be an attenuator of the deleterious effect of salinity on the radish crop. The aim was to evaluate the effectiveness of a biostimulant based on amino acids and freshwater algae extract on radish (Raphanus sativus L.) cultivated under irrigation conditions with saline water. The experiment was carried out in a greenhouse. The saline levels evaluated were 0.15, 1.8, and 2.8 dS.m-1 and four doses of biostimulant were applied (0, 2, 4, and 6 mL/L). The statistical design was completely randomized, in a 4x3 factorial scheme with 4 replications. Biometric and biomass analyses, sodium and potassium contents, and soluble solids were performed. Was observed that plants submitted to high salinity levels (2.8 dS m-1) with application of 6mL/L of the biostimulant showed high values in height (12.2 cm), stem (5mm) and tuber (6mm) diameter, leaf area (50cm2), fresh and dry mass of aerial part (3.5 g) and underground system (5.8 g). The application of the biostimulant 6 mL/L, at the salinity level of 2.8 dS.m-1, favored the increase of saline ions in the tuber of the plants. The application the biostimulant provided a higher content of soluble solids. Applications of the biostimulant in plants with saline stress showed beneficial responses in the performance of the radish, therefore the dose of 6 mL/L is recommended for a satisfactory response of the performance of the radish in saline conditions.